“Start-up Strategy of CSR focused Companies” - Sharma, Aakarsh (2013)
This research focuses on analysing the start up strategies followed by a CSR (corporate social responsibility) focused company. Research is conducted by using a case study analysis method and analysing the strategies followed by three popular CSR focused companies in the UK. Findings reflect the clarity of a social and environmental vision of these companies from the beginning and the stress they lay on educating the customers about their products and its benefits. These companies usually produce innovative and creative products and this coupled with the social and environment friendly aspect outclass the competitor’s products.